2010
DOI: 10.3310/hta14440
|View full text |Cite
|
Sign up to set email alerts
|

Group cognitive behavioural therapy for postnatal depression: a systematic review of clinical effectiveness, cost-effectiveness and value of information analyses

Abstract: E Kalthenthaler and the group cognitive behavioural therapy for postnatal depression advisory groupHow to obtain copies of this and other HTA programme reports An electronic version of this title, in Adobe Acrobat format, is available for downloading free of charge for personal use from the HTA website (www.hta.ac.uk). A fully searchable DVD is also available (see below).Printed copies of HTA journal series issues cost £20 each (post and packing free in the UK) to both public and private sector purchasers from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
62
1
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(66 citation statements)
references
References 38 publications
0
62
1
1
Order By: Relevance
“…There were two studies for which multiple papers for the same study were found 45,57,392,393 and in both cases the more detailed paper was selected. 45,392 An additional paper that was published after the search was completed was identified by a member of the project team who was an author on the paper and the paper was included. 396 It was not identified in a systematic way and other papers that were published after the search was conducted will have been missed.…”
Section: Study Selection Criteria and Procedures For The Health Economentioning
confidence: 99%
See 3 more Smart Citations
“…There were two studies for which multiple papers for the same study were found 45,57,392,393 and in both cases the more detailed paper was selected. 45,392 An additional paper that was published after the search was completed was identified by a member of the project team who was an author on the paper and the paper was included. 396 It was not identified in a systematic way and other papers that were published after the search was conducted will have been missed.…”
Section: Study Selection Criteria and Procedures For The Health Economentioning
confidence: 99%
“…397 It had been excluded at the title and abstract stage as PND or associated terms were not included in the title or abstract. Of the 13 papers identified, 61,174,199,264,[392][393][394][398][399][400] nine described an economic evaluation that was conducted alongside a trial, 53,61,174,199,264,299,392,393,400 three papers described an economic decision model 45,56,394 and one paper described a cost study. 398 …”
Section: Study Selection Criteria and Procedures For The Health Economentioning
confidence: 99%
See 2 more Smart Citations
“…Por tal razón, algunos autores han propuesto la TCC de grupo para reducir los costos y las listas de espera, pero los datos de estudios que apoyen dicha alternativa son todavía escasos y no permiten extraer conclusiones ciertas o indicar guías de tratamiento basadas en evidencia (69).…”
Section: Introductionunclassified